2001
DOI: 10.1002/1521-3765(20010601)7:11<2324::aid-chem23240>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 5-Azacastanospermine, a Conformationally Restricted Azafagomine Analogue

Abstract: The 5-aza-6-deoxy analogue of castanospermine (+/-)-5a and its 1-epimer (+/-)-5b was synthesized. The synthesis started from the known compound 5-benzyloxy-7-hydroxyhepta-1,3-diene, which was protected and subjected to Diels-Alder reaction with 4-phenyl-1,2,4-triazoline-3,5-dione to give two epimeric adducts. One of these was transformed through epoxidation, acetolysis, a series of side-chain transformations that converted it into a terminally protected aldehyde, deprotection, and hydrogenolysis/reductive amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…The epimer of 26, 30 having the hydroxyl group of the five-membered ring at the equatorial position showed poorer values to the same enzymes: between K i = 570 -690 M, except for -glucosidase from rice to which the value is even poorer K i >1000 M. This strongly suggests a clear preference of glucosidases for binding substrates with the hydroxy group at the axial position [18]. ( Figure 5) Azagalactofagomine 39 was tested against a series of glycosidases.…”
Section: Synthesis Of 1-azafagomine and Monocyclic Analoguesmentioning
confidence: 99%
See 1 more Smart Citation
“…The epimer of 26, 30 having the hydroxyl group of the five-membered ring at the equatorial position showed poorer values to the same enzymes: between K i = 570 -690 M, except for -glucosidase from rice to which the value is even poorer K i >1000 M. This strongly suggests a clear preference of glucosidases for binding substrates with the hydroxy group at the axial position [18]. ( Figure 5) Azagalactofagomine 39 was tested against a series of glycosidases.…”
Section: Synthesis Of 1-azafagomine and Monocyclic Analoguesmentioning
confidence: 99%
“…Synthesis of fused bicyclic azafagomine analogues (castanospermine analogues)Two epimers of 5-aza-6-deoxycastanospermine analogues were obtained through Diels-Alder cycloaddition in the first step, from 5-benzyloxy-7-acetoxyhepta-1,3-diene 18 and PTAD[18].Scheme Cycloaddition of the diene 18 to PTAD. epimeric adducts ()-19 and ()-20 underwent functional group transformations to give the azacastanospernine analogues.…”
mentioning
confidence: 99%
“…13b), has recently been published with full discussion and experimental details. 29 Finally, the sulfonium salt (ϩ)-52 was prepared in order to test a hypothesis that the inhibition of glycosidases by hydroxylated indolizidine alkaloids might arise from electrostatic stabilisation of positively charged species in the enzymes' active site. 24 The four racemic castanospermine isomers 42-45 proved to be moderate inhibitors of a recombinant α-1,6-fucosyl- transferase from Rhizobium sp.…”
Section: Castanospermine and Related Compoundsmentioning
confidence: 99%
“…27, 28 The (±)-5-azacastanospermine analogue 50 was found to be a weaker inhibitor of almond β-glucosidase and rice α-glucosidase than castanospermine, but nonetheless substantially more potent than its 1-epimer 51. 29 Finally, the sulfonium salt (ϩ)-52 was prepared in order to test a hypothesis that the inhibition of glycosidases by hydroxylated indolizidine alkaloids might arise from electrostatic stabilisation of positively charged species in the enzymes' active site. 30 X-Ray crystallography and NMR spectroscopy showed that the preferred conformation of the salt both in the solid state and solution was as shown in 53, with the three hydroxy groups all axial.…”
Section: Castanospermine and Related Compoundsmentioning
confidence: 99%
“…11 Our long-standing interest in glycosidase inhibitors of the isofagomine-type 12 (4, Fig. 2) has led us to consider conformationally restrained analogues 13 as a means of providing information about the binding of these inhibitors. The isofagomines are strong β-glycosidase inhibitors.…”
Section: Introductionmentioning
confidence: 99%